Formulating Cream of Dumbo Catfish Skin Extract (Clarias Gariepinus) for Acceleration of Slice Wound Healing in White Male Rats (Rattus Novergicus) Wistar Straight - Nurjannah Mopangga; Muh. Aprianto Paneo; Srimuliani Arbie (Journal of Health, Technology and Science (JHTS), 2021)
Wound is a condition in which the skin tissue is damaged and some of the skin tissue is lost. Catfish skin is one part that contains collagen.One of the ingredients that has been widely used to maintain a moist atmosphere in wounds is collagen This study aimed to determine the effect of African catfish skin extract cream to determine the effectiveness of collagen from catfish skin extract in accelerating the healing process of cuts in male white rats. The method in this research is experimental laboratory using one sample t-test test data analysis to see the effect of the catfish skin extract cream formula. The research design used was a post test only control group. The experimental group was treated by giving the catfish skin extract cream formula, while the negative control group was not given any treatment. Each cream formula has three concentrations, namely 5%, 7.5% and 12.5% ​​and cream base as a negative control. The results showed that the cream formulation with a concentration of 12.5% ​​had an effect on wound healing on the seventh day, this was seen from physical observation by looking at the changes in the length of the wound which was reduced and the wound had dried. African catfish skin cream has an effect on wound healing with a healing process within 7 days The effectiveness of African catfish skin cream at a concentration of 12.5% ​​has a faster effect on wound healing compared to the 7.5% and 5% formulas